Brain information processing of football players during decision making - Matsutake, T.; Natsuhara, T.; Tabei, Y.; Nakayama, M.; Asai, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In soccer, there are many situations in which decision making for instantaneous judgments is required. The main research method in this area has been measuring the Reaction Time (RT) and visual search behavior (Ando et al., 2001; Montes-Mico et al., 2000). It has been argued that RT is an elapsed time from the perceived stimulus to the action, and visual search behavior involves cognitive behavior. For that reason, only analyzing these two indicators, will not produce adequate considerations for how soccer players process information during decision making. The purpose of this study, therefore, was to clarify the differences in information processing process of football players with different performance level. Methods: Participant were college football players who were winners of the all Japan university top level (n = 5; Expert) and 5 graduate students with no football experience (n = 5; Novices). They used a decision making task (Soccer version). Electroencephalography (0.5-100 Hz) was recorded with Ag/AgCl electrodes from 5 scalp locations: Fz, Cz, Pz, C3, C4. Trials with eye blinks, eye movements and response errors were excluded from analysis (±80 mV).EMG-RT is the time from stimulus.. onset to the appearance of the electromyogram (EMG). EMG-RT is a valid.. indicator of programming time. the electrode is mounted the surface of the gastrocnemius lateral head. Results: P300 was identified at the latency and from the polarity to induced latent, latency and amplitude were also measured. In all of the participants of the experiments and the tasks, P300 has been confirmed. EMG-RT has appeared before the P300 latency in all participants. Expert had a significantly shorter RT and EMG-RT than Novices in the task. Discussion: The result of this study identified the trend that EMG-RT has appeared before the P300. The human brain always predicts the future and it changes the behavior by calculating the consistency of the results. Rather than to predict and evaluate by a command from the brain, it can be evaluated from the receiving sensation (Seth, A. K. , 2013). This is called the interoceptive inference, and it has attracted attentions in recent years. The results of this study, did not agree with the results of previous studies on the ERP and EMG. For that reason, it can be considered that it is likely to be associated with the interoceptive inference. In future studies, number of participants need to be increased for more reinforced considerations.